2021
DOI: 10.15537/smj.2021.1.25588
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anosmia among COVID-19 patients in Taif City, Kingdom of Saudi Arabia

Abstract: Objectives: To assess the prevalence of anosmia in coronavirus-19 (COVID-19) patients. Coronavirus-19-related anosmia and hyposmia is a new emerging concept in the medical literature. Methods: A retrospective study on COVID-19 patients with anosmia and hyposmia was performed during the period between May-July, 2020. The inclusion criteria were all clinically stable COVID-19 patients >15 years old with positive reverse transcription-polymerase chain reaction (RT-PCR). Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…Interestingly, the present study found that patients with smell affection were significantly younger than patients with normal smell, which is in line with the former study of Mubaraki et al 13 …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Interestingly, the present study found that patients with smell affection were significantly younger than patients with normal smell, which is in line with the former study of Mubaraki et al 13 …”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, the present study found that patients with smell affection were significantly younger than patients with normal smell, which is in line with the former study of Mubaraki et al 13 In this study, we assessed the relation between vitamin B12 levels and smell affection scores in COVID-19 patients. In the first and 4 weeks, groups with higher vitamin B12 levels had significantly better self-rated smell affection scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is great variability in the figures of OGD across the studies, reaching up to 74% [3][4][5][6][7][8]16]. Despite this discrepancy, both anosmia and ageusia were consistently defined as typical clinical features for COVID-19 infection and attracted much attention.…”
Section: Discussionmentioning
confidence: 99%
“…Among these atypical signs, olfactory and gustative dysfunctions (OGDs) were identified as hallmarks of SARS-COV-2 infection since the start of the pandemic and had a high diagnostic value, notably for paucisymptomatic cases [3]. Although described as common since the early series of cases, the prevalence of OGDs varied greatly, ranging between 6% up to 70% [3][4][5][6][7][8]. These symptoms are characterized by partial (hyposmia and hypogeusia) or total (anosmia and ageusia) loss of the senses of smell and taste, respectively, and were mainly reported in the acute phase of the disease, either isolated, preceding, or associated with other symptoms such as fever, dry cough, or headache [6,9,10].…”
Section: Introductionmentioning
confidence: 99%